Keratin:Zein particles as vehicles for fragrance release on hair - Tinoco, Ana (2021)
Hair perfumes are becoming a trend all over the world and new cosmetic formulations have been developed to address this recent need. In the present study, we developed a system for the controlled delivery of perfumes on hair, based on zein, a protein derived from maize, and on keratin. The Keratin:Zein particles, obtained using different strategies and proportions of zein and keratin, presented a high stability along storage, related with the presence of keratin on the particles formulation. When applied on hair, the particles formed a film-like structure over the fibers. Fragrance diffusion from the hair-coated particles was dependent on the temperature, the method of particles preparation and the fragrances physicochemical properties (melting point and vapor pressure). The particles formulations showed also the capacity to improve hairs mechanical properties and hydration degree. The new system based on Keratin:Zein particles revealed high potential for the development of personalized hair cosmetic products allowing adjustments depending on the personal sensory preferences.